The South African Media’s coverage of the Abu Ghraib Prisoner abuses: an ethical case study of two selected newspapers - Buchinger, Christine (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Journalism))--University of Stellenbosch, 2006.